The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1114/b:abme.0000042226.97347.de
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Thermal Denaturation of Proteins in Dunning AT-1 Prostate Cancer Cells: Implication for Hyperthermic Cell Injury

Abstract: The in situ thermal protein denaturation and its correlation with direct hyperthermic cell injury in Dunning AT-1 prostate tumor cells were investigated in this study. The in situ thermal protein denaturation was studied using both Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). The FTIR spectra at different temperatures show changes in protein secondary structure (from alpha helix to extended beta sheet) during in situ thermal protein denaturation within AT-1 cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 46 publications
5
103
0
Order By: Relevance
“…Although cells attached to cell-culture-treated substrate has been dominantly used in studies on thermally induced cell injury, cells suspended in media have also been used to investigate the protein and lipid change in intact cells. 6,24,31,32,46 Therefore, it is interesting and important to compare the thermal injury behavior between suspended and attached cells. Some studies reported that suspended bacterial cells are more susceptible to heat than attached ones, 12,16 such study on mammalian (tumor) cell lines has not been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Although cells attached to cell-culture-treated substrate has been dominantly used in studies on thermally induced cell injury, cells suspended in media have also been used to investigate the protein and lipid change in intact cells. 6,24,31,32,46 Therefore, it is interesting and important to compare the thermal injury behavior between suspended and attached cells. Some studies reported that suspended bacterial cells are more susceptible to heat than attached ones, 12,16 such study on mammalian (tumor) cell lines has not been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…5,9,10 The irreversible denaturation of proteins is assumed to be the ratelimiting step in heating-induced tissue coagulation and also has been shown to be directly correlated with cell death. [11][12][13] Tissue damage can be modeled as a change in state based on an Arrhenius rate process.…”
Section: Introductionmentioning
confidence: 99%
“…The fitting was done with a non-linear optimization procedure (the flexible tolerance method 28 ) to minimize the root mean square between the model predictions and the experimental data, which has been used by the authors in a number of studies to extract multiple parameters in a variety of models for various applications. 22,23,25,26 …”
Section: Determination Of Model Parametersmentioning
confidence: 98%